Rancangan alat bantu untuk perbaikan postur tubuh pada bengkel shockbreaker motor bekasi - Rangkuti, Indra Yusuf; Tresia, Lucyana; Salati, Dianasanti; Imdam, Irma Agustiningsih; Achsan, Muhammad Fathur; Megarukmana, Vivaldhi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
With the growth of the economy and market demand, Micro, Small and Medium Enterprises (MSMEs) play a significant role in economic development by providing employment opportunities and enhancing local economic growth, typically through small-scale production by artisans and small producers. UMKM XYZ is a small-scale service business specializing in motorcycle shock absorber repairs, employing three workers. In this workshop, issues related to workers' postures were identified, which caused discomfort and potential health problems. The Rapid Entire Body Assessment (REBA) method was utilized to evaluate the workers' body posture, including the positions of the neck, back, arms, wrists, and legs. Consequently, sample data were collected and analyzed to implement improvements in the shock absorber repair process. An assistive tool was designed as a proposed solution to improve workers' postures to be more ideal, resulting in lower REBA scores.